An Image Encryption Algorithm Based on Improved Lifting-Like Structure and Cross-Plane Zigzag Transform - Haixiao Li; Yinan Hu; Ziming Shi; Bin Wang; Pan Zheng (IEEE Access, 2022)
With the increasing development of information technology, image information security has received more and more attention. Furthermore, image encryption is one of the most powerful methods to ensure image information security and plays a vital role in modern society. This paper proposes an image encryption algorithm based on an improved lifting-like structure and cross-plane zigzag transform. First, to overcome the problem of simple original lifting-like structure and single update function. We modularize the original image and add new update functions and prediction functions to handle the information between different modules. Our proposed structure has higher encryption quality and can better spread the information between each image pixel. Secondly, we propose a cross-plane zigzag transform, which can effectively eliminate the correlation between adjacent elements of the original image by applying the zigzag transform to the replacement between different planes, overcoming the disadvantage that the traditional zigzag transform is limited in scanning mode and challenging to resist brute-force attack. The experimental results show that compared with other state-of-the-art schemes, this scheme has higher information entropy, can well resist selective plaintext attacks and differential attacks, and has better security.